Analisis Yuridis Bahaya Narkotika bagi Kesehatan Masa Depan Generasi Muda - Nasrianti N; Muhibbuddin M (LPPM Universitas Malikussaleh, 2020)
Abuse of Narcotics among the younger generation which can damage health and destroy the future of the younger generation and also the continuation of the future of the State then in legal considerations the birth of Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics is, to create a prosperous, just and prosperous Indonesian society that is evenly material and spiritual based on Pancasila and the 1945 Constitution of the Republic of Indonesia, the quality of Indonesia's human resources as one of the assets for national development needs to be continuously maintained and improved, including the degree of health; Therefore, to improve the health status of Indonesian human resources in the context of realizing the welfare of the people, it is necessary to make efforts to improve in the field of treatment and health services, among others by seeking the availability of certain types of Narcotics which are urgently needed as drugs and to prevent and eradicate the dangers of abuse and illicit Narcotics trafficking and Narcotics Precursor. The method used in this research is a qualitative normative juridical research method, namely a research method that refers to the legal norms contained in legislation. The conclusion of Articles 18 and 19 of Law of the Republic of Indonesia Number 36 of 2009 concerning Health, states that the Government is responsible for empowering and encouraging the active role of the community in all forms of health efforts, and the Government is responsible for the availability of all forms of quality, safe health efforts. efficient, and affordable.